1999
DOI: 10.1161/01.atv.19.11.2701
|View full text |Cite
|
Sign up to set email alerts
|

A Hepatic Lipase Gene Promoter Polymorphism Attenuates the Increase in Hepatic Lipase Activity With Increasing Intra-abdominal Fat in Women

Abstract: Abstract-High hepatic lipase (HL) activity is associated with an atherogenic lipoprotein profile of small, dense LDL particles and lower HDL 2 -C. Intra-abdominal fat (IAF) is positively associated with HL activity. A hepatic lipase gene (LIPC) promoter variant (G3 A Ϫ250 ) is associated with lower HL activity, higher HDL 2 -C, and less dense LDL particles.To determine whether the LIPC promoter polymorphism acts independently of IAF to regulate HL, 57 healthy, premenopausal women were studied. The LIPC promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
41
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 61 publications
7
41
0
1
Order By: Relevance
“…In this study we found that both IAF and adiponectin were major correlates of plasma lipoproteins, in particular of LDL buoyancy (Rf) and HDL cholesterol concentrations, in keeping with other reports [31,34,64]. These relationships could be mediated by effects of adiponectin on hepatic lipase activity, which is increased in central obesity and insulin resistance states associated with the metabolic syndrome [65,66]. While hepatic lipase does not seem to be acutely regulated by insulin [67], it could be increased by reduced adiponectin concentrations.…”
Section: Discussionsupporting
confidence: 91%
“…In this study we found that both IAF and adiponectin were major correlates of plasma lipoproteins, in particular of LDL buoyancy (Rf) and HDL cholesterol concentrations, in keeping with other reports [31,34,64]. These relationships could be mediated by effects of adiponectin on hepatic lipase activity, which is increased in central obesity and insulin resistance states associated with the metabolic syndrome [65,66]. While hepatic lipase does not seem to be acutely regulated by insulin [67], it could be increased by reduced adiponectin concentrations.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with this is the fact that HL activity is higher overall in men than in women (4) and is higher with central obesity (11,12). HL is produced primarily by the liver and is located on the luminal surface of sinusoidal endothelial cells.…”
mentioning
confidence: 62%
“…In this model, the cholesterol concentration in the fractions corresponding to VLDL (fractions 31-38), IDL (fractions 29 and 30), buoyant LDL (fractions [12][13][14], dense LDL (fractions 7-9), and HDL (fractions 1-5) was associated with IAF, whereas S I made no additional contribution to any of the fractions. In a third model, we included BMI as an independent variable together with IAF, S I , and SCF, and found that the cholesterol concentration in the fractions corresponding to VLDL (fractions [31][32][33][34][35][36][37][38], IDL (fraction 30), and dense LDL (fractions 8 -10) was associated with IAF, whereas S I again made no additional contribution. Thus IAF, but not S I , had independent effects to determine the cholesterol concentration beyond those of SCF and BMI.…”
Section: Dj Nieves and Associatesmentioning
confidence: 99%
“…Thus an increase in the waist-to-hip ratio (WHR) has been found to be associated with small dense LDL particles (26), as has been an increase in IAF mass (27,28) or insulin sensitivity (29,30). This pattern of central fat distribution has also been associated with an increase in VLDL and intermediate-density lipoprotein (IDL) (26,31) and a decrease in HDL 2 cholesterol (26,32,33). Although these analyses strongly suggest that central fat distribution and/or insulin resistance is an important determinant of adverse changes in lipoprotein profile, we believed that a critical examination of this issue in a large number of apparently healthy subjects was required to determine the impact of differences in body fat distribution and insulin sensitivity on plasma lipids.…”
mentioning
confidence: 99%